Role of Public Financial Governance Practices on the Performance of Kisumu County Government - Otieno, Jared; Tefera, Orthodox (International Journal of Finance and Accounting, 2025)
Purpose: The study sought to analyze the effect of public financial management practices on the performance of the Kisumu County Government. It entailed assessing how auditing, information technology, regulation, and public engagement in decision-making affect the performance of Kisumu County Government. Methodology: The study employed Systems Theory as the framework for developing the survey. The target group consisted of 70 participants from Kisumu County Government, such as ICT officers, accountants, finance officials, auditors, the County Secretary, and ward administrators. Data collected from the field were analyzed using the Statistical Package for the Social Sciences (SPSS) through both descriptive and inferential analyses. The results were analyzed and recorded in tabular form. Findings: All the examined aspects were identified to have a significant effect on the KCG performance; however, auditing practices had the most significant effect compared to information technology, public participation, and regulatory policies. Thus, based on the research outcomes, several factors, such as the explicit possibility of auditing to build trust and identify risks and control issues, affect the efficiency of county governments. In addition, meetings and hearing sessions that involve the public provide input in the budgeting process, enhancing performance. Unique Contribution to Theory, Practice and Policy: The study recommends that county governments should adopt and follow proper financial structures and processes as stated in the legislation as contained in the Public Financial Management Act. The processes are often audited to ensure compliance and effectiveness.